Vazio e subjetividade: retratos da infância nas graphic novels de Neil Gaiman e Dave Mckean - Kurowsky, Kleber (2018)
Childhood is one of the constant themes in Neil Gaiman’s narratives, manifesting itself in several textual genres. Deprived of nostalgia, childhood, in the works of Gaiman, is a menacing environment, of insecurity, uncertainty: children know very little of the world and what they know only inspire fear. This becomes even more clear in the works narrated in first person about recollections of childhood; the narrators can’t point exactly what happened in their past, creating gaps in their memories. Through this, the fantastic element manifests itself in the narratives: maybe, amidst the remembered events, there are fantastic aspects, something supernatural, or maybe it’s just the results of the gaps in their memories. Being that Gaiman is know for his work in comics – mainly for Sandman (1989 – 1996) -, it doesn’t cause surprise that this game between memory and childhood also appear in this genre. It is the case of the works that are objects of this research, Violent Cases (1987) and Mr. Punch (1994): both illustrated by Dave McKean, they deal with a adult narrator remembering events of their childhood, which they are not sure really happened. With this in mind, the research proposed in this dissertation offers a discussion about how the gaps in the memories of the narrators manifests themselves in the works, and how the unique language of comics expose said gaps to the reader: emptiness and forgetfulness, therefore, is the main theme of debate. For that we’ll create a dialogue between literary theory and comics theory to observe how this theories relate to one another and, through this, study how the emptiness is used in the mentioned works, pointing out where they approach each other and where they depart, starting from the hypothesis that there is some kind of correlation between the empty spaces between the panels – know as ‘gutter’ – and the forgetfulness of the narrators.